Synchronous Rectification Voltage Regulator Module For Low Voltage DC/DC Converter. - How , Chee Hua (2003)
New generation microprocessors reguire power supply system with high current capability, fast transient reponse, and tight voltage regulation, which hardly can be satisfied by conventional power converter. As a result, they require a new innovative architecture, Voltage Regulator Module(VRM), to provide well-regulated voltage. This project presents the analysis, design, and performance evaluation of a multiphase synchronous buck VRM with adaptive voltage positioning technique in applications to distributed power supply system.